Hepatitis B virus genotypes and mutations affecting HBeAg production: A Malaysian perspective - Chee, Kent Lim; So, Har Ton (Penerbit UKM, 2007)
Infection by hepatitis B virus (HBV) is a major global health-care problem. HBV is an accepted factor in the elevated risks for liver disease such as cirrhosis and development of hepatocellular carcinoma. This problem is particularly prevalent in the Asia-Pacific region which includes Malaysia. During infection, the hepatitis B e antigen (HBeAg) is produced in the hosts. This antigen is an important serological marker for diagnosing chronic hepatitis B. Seroconversion to anti-body (anti-HBe) corresponds to the improvement of disease prognosis. However, certain mutations such as the core promoter dual mutations (A1762G1764→T1762A1764), the codon 15 variants (C1858/ T1858) and the precore stop codon mutations (TGG→TAG) can affect the HBeAg expression. This has diagnostic and clinical implications. Besides that, the HBV can be grouped into eight genotypes (A to H).Moreover, genotypic subtypes and recombinants have been observed as well. Studies have observed that these can differ in their affiliations with the mutations above as well as with disease prognosis